Meat consumption and racial/ethnic disparities in population-based study in the city Campinas, Brazil - Samara Agda dos Santos; Josiane Steluti; Natália Simonian Rodrigues Valente Ghedini; Semíramis Martins Álvares Domene (Revista Brasileira de Estudos de População)
Abstract The aim of the present study was to investigate meat consumption among adults residing in a city in the countryside of São Paulo, Campinas, according to ethnicity/skin color in two periods: 2008/2009 and 2014/2015, given the scarce literature on the subject. Thus, we sought to evaluate the association between race/color and consumption of meat, a food of great cultural value, based on the hypothesis that this demographic marker is relevant to explain food choices. A cross-sectional population-based study evaluating participants from the Health Survey of the City of Campinas (ISACAMP) was conducted in 2008/2009 and 2014/2015, with 2,354 and 1,606 individuals respectively, aged 20y or older. Food consumption data were collected using the 24-hour food recall method and meats were classified according to animal origin and type of processing. Linear regression models were run to assess the association between meat consumption and sociodemographic variables with a significance level of 5%. Lower total consumption of meat, red meat, beef and fish was found among individuals with self-declared black skin color compared to those with self-declared white skin color. Red meat consumption varied from 109.4g to 157.9g in 2008/2009 and from 102.1g to 125.1g in 2014/2015 between the groups, remaining above the recommendation in both periods. The World Cancer Research Fund recommends consuming between 50 and 71.4 g/day of red meat; thus, these findings reinforce the importance of studies that investigate the impact of ethnicity on food consumption, since racial disparities may be in the origin of the insufficient or excessive consumption of certain types of meat, and understanding the factors associated with the consumption of types of meat is relevant for the adoption of health actions aimed at adequate food intake.